Pengaruh Kompensasi, Locus of Control dan C Terhadap Kinerja Pegawai di Dinas Ketenagakerjaan dan Transmigrasi Provinsi Sumatera Barat - Aminar Sutra Dewi; Muhammad Andika (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
This study aims to examine the effect of compensation, locus of control, and self efficacy on employee performance. The sampling technique used in this study was total sampling. The research sample was employees of the Manpower and Transmigration Office of West Sumatra Province. Where the number of employees at the Manpower and Transmigration Office was 40 people and all samples were sampled in this study. Data collection was carried out using the documentation method and literature study. The data analysis technique used is the Classical Assumption Test and Hypothesis Test using multiple linear regression using SPSS 26. The results showed that: (1) Compensation has a positive and significant effect on employee performance, (2) Locus of control has a positive and significant effect on employee performance. (3) Self efficacy has a positive and significant effect on employee performance.